Functional Intricacy and Symmetry of Long Non-Coding RNAs in Parasitic Infections - Olajide, Joshua Seun; Olopade, Bolatito; Cai, Jianping (Frontiers in Cellular and Infection Microbiology, 2021)
RNAs are a class of molecules whose vast majority in eukaryote are arbitrarily termed non- coding transcripts and broadly classified as short and long non-coding RNAs. Of recent, identification and functions of long non-coding RNAs have continued to accumulate as important molecules that regulate parasite-host interface, parasite differentiation, host responses and disease progression. Herein, we present and integrate the functions of host and parasite long non-coding RNAs during infections within the context of epigenetic re-programming and molecular crosstalk in the course of host-parasite interactions. Also, the modular range of parasite and host long non-coding RNAs in coordinated parasite developmental changes and host immune dynamic landscapes are discussed respectively. We equally canvass the prospects of long non-coding RNAs in disease diagnosis and prognosis. In finale, hindsight and suggestions are offered with the aim that it will bolster our understanding for future works on host and parasite long non-coding RNAs.